Mass extinctions and the climate - Pacheco, José Antônio de Freitas (Cadernos de Astronomia, 2025)
In this article are discussed the main causes suspected to be responsible for the massive extinction of species during the  last 600 million years of the Earth’s history. Generally, cosmic catastrophes and volcanism have been invoked as the main  reasons. However, in the present days, there is a consensus  among experts that these extinction episodes are due to multiple causes, which modify the habitat, in particular the  climate, in a short timescale. Consequently, species do not  have enough time to adapt themselves to the new  environment and disappear. There are indications that we are  in the dawn of a new massive extinction that may have severe  implications for the surviving of the humanity.
Keywords: Mass extinctions; climate change; life on Earth